Properties of Biochar Derived from Tea Waste as an Alternative Fuel and Its Effect on Phytotoxicity of Seed Germination for Soil Applications - Tunklová, Barbora; Jeníček, Lukáš; Malaťák, Jan; Neškudla, Michal; Velebil, Jan; Hnilička, František (Materials (Basel, Switzerland), 2022)
Tea waste as a potential biofuel and bio fertilizer was analyzed. Samples were collected from various tea species and torrefied to five different temperatures. All samples were analyzed for their proximal composition and calorific value. From the results, stoichiometric properties were calculated. A phytotoxicity test was performed, and the germination index was measured. Tea waste torrefied at 350 °C may be suitable biofuel reaching the calorific value of 25-27 MJ kg-1, but with quite a high share of ash, up to 10%, which makes its use technically challenging and may lead to operating issues in a combustion chamber. The same biochar may be a suitable fertilizer for increasing the germination index, therefore, applicable to the soil. The non-torrefied sample and the sample treated at 250 °C are not suitable as fertilizers for being toxic. The total phenolic content in waste black tea was reduced from 41.26 to 0.21 mg g-1, depending on the torrefaction temperature. The total flavonoid content was also reduced from 60.49 to 0.5 mg g-1. The total antioxidant activity in the non-torrefied sample was 144 mg g-1, and after torrefaction at 550 °C, it was 0.82 mg g-1. The results showed that black tea waste residues have the potential for further use, for example, in agriculture as a soil amendment or as a potential biofuel.
Keywords: biofuel; phytotoxicity; biomass; calorific value; biochar; tea waste